Time Management Analysis on the Terban Market Renovation Project in Yogyakarta - Panca setiawan; Alizar Alizar (Asosiasi Dosen Muda Indonesia, 2025)
The construction of the Terban Market in Yogyakarta requires time management that not only sharpens priorities but also enhances the efficiency and effectiveness of project execution. This study aims to analyze the application of time management in the Terban Market construction project, with a focus on improving prioritization, efficiency, and effectiveness. The research method used is Earned Value Analysis (EVA) to evaluate project performance in terms of time and cost. Data were obtained through field observations and interviews as primary data, and project documents such as the S-Curve and Budget Plan (RAB) from the contractor as secondary data. The analysis results indicate that time management implementation still requires improvement, particularly in on-site execution, with several weaknesses identified during project implementation.